Effect of VSD combined with antibacterial dressing on wound healing of diabetes foot ulcer after artificial dermis transplantation - WU Yan-hong; ZHANG Li-ming; WANG Yu-zhi; CHEN Jian-wu; ZHANG Bin; TANG Jian-bing; CHENG Biao (Zhongguo linchuang yanjiu, 2022)
Objective To investigate the effect of vacuum sealing pressure drainage（VSD） combined with antibacterial dressing on wound healing and the expression of transforming growth factor β1（TGF-β1） and cyclin D1 in granulation tissue of diabetes foot ulcer after artificial dermis transplantation. Methods From January 2019 to June 2021, 60 patients with diabetes foot who were treated in the Burn and Plastic Surgery Department of General Hospital of Southern Theatre Command were selected and randomly divided into the control group and the observation group randomly(n=30, each). The patients in the control group received artificial dermis transplantation; On the basis of the control group, the patients in the observation group were treated with VSD and alginate dressing. The wound appearance of the two groups was observed. The levels of basic fibroblast growth factor(bFGF), epidermal growth factor (EGF) and vascular endothelial growth factor(VEGF) in serum, wound area, VAS score, and the levels of cyclin D1, TGF-β1 in wound tissue were measured. The exudates of the two groups were cultured for bacteria. Results The patients were followed up for 3 months. During the follow-up period, there was no ulcer recurrence in the observation group, but 5 cases in the control group. The scar hyperplasia of the patients in the observation group was light, and the skin had better elasticity and integrity. After treatment, the wound area of both groups was reduced, and that of the observation group was less than that of the control group(P＜0.05). After treatment, the coverage area and coverage rates of granulation tissue in the two groups were increased compared with those before treatment, and the observation group were higher than the control group(P＜0.05). After treatment, the VAS scores of patients in both groups decreased(P＜0.05), and the observation group was lower than that in the control group(P＜0.05). After treatment, the levels of serum bFGF, EGF and VEGF in the two groups increased(P＜0.05), and those in the observation group were higher than those in the control group at each time point(P＜0.05). After treatment, 5 strains of bacteria were cultured in the observation group, the bacterial infection rate was 13.33%(4/30), and 9 strains were cultured in the control group, the bacterial infection rate was 36.67%(11/30). The bacterial infection rate in the observation group was lower than that in the control group(P＜0.05). After treatment, the levels of cyclin D1 and TGF-β1 in wound tissues of both groups increased, and those in the observation group waere higher than those in the control group(P＜0.05). Conclusion VSD combined with antibacterial dressing has a significant effect on wound healing of diabetes foot ulcer after artificial dermis transplantation, which can increase the levels of Cyclin D1 and TGF-β1 in granulation tissue of patients, and increase the levels of bFGF, EGF and VEGF in serum.